2015
DOI: 10.1097/qad.0000000000000695
|View full text |Cite
|
Sign up to set email alerts
|

‘HIV is like a tsotsi. ARVs are your guns’

Abstract: Early and full disclosure is strongly associated with improved adherence amongst ART-initiated adolescents. Disclosure may be an essential tool in improving adolescent adherence and reducing mortality and onwards transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 36 publications
5
53
2
1
Order By: Relevance
“…Furthermore, we found an improved mean CD4 count with a younger age of disclosure (conversely, delayed disclosure predicts a lower mean CD4 count, as the correlation and regression models illustrate). Our findings are consistent with previous qualitative and cross-sectional studies that have described improved adherence with disclosure[8,11,12,14,18,22,26,29,30]. Far fewer longitudinal studies, such as ours, have looked at the associations between disclosure and adherence or outcomes over time[9,23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we found an improved mean CD4 count with a younger age of disclosure (conversely, delayed disclosure predicts a lower mean CD4 count, as the correlation and regression models illustrate). Our findings are consistent with previous qualitative and cross-sectional studies that have described improved adherence with disclosure[8,11,12,14,18,22,26,29,30]. Far fewer longitudinal studies, such as ours, have looked at the associations between disclosure and adherence or outcomes over time[9,23].…”
Section: Discussionsupporting
confidence: 92%
“…Quantitative studies and outcomes data are far less prevalent; one study done in Romania showed that a patient’s knowledge of his or her HIV infection was related to delayed disease progression[23], while an adherence study in Zambia showed a positive correlation between adherence to ART and knowledge of one’s own HIV infection in young adolescents[9]. A recent study in West Africa showed an improved retention in care when adolescents were aware of their HIV status[25], and a cross-sectional study in South Africa showed that early and full disclosure was strongly associated with ART adherence[26]. Given the paucity of research on the medical benefits or drawbacks to HIV disclosure to adolescents, and the growing number of ALHIV, there is an urgent need to assess the medical outcomes of disclosure of HIV infection to those patients.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when evaluating continuous measures of VL and adherence, we saw improved adherence measurements preceding improvements in VL. Although nonintervention studies have also shown that disclosure of HIV status is associated with improved adherence to ART regimens among children and adolescents, 6,10 our study is the first to evaluate changes in adherence longitudinally before and after the introduction of a disclosure intervention.…”
Section: Discussionmentioning
confidence: 97%
“…Of the 13 disclosure intervention studies they identified, only one was concerned with disclosure to children, focusing in particular on maternal HIV status disclosure to HIV-uninfected children [32]. Cluver et al [33] extended the evidence base regarding the important benefits of HIV status disclosure, and their study in South Africa showed that early and full disclosure of HIV status for perinatally infected adolescents was strongly associated with improved treatment adherence.…”
mentioning
confidence: 99%